2012
DOI: 10.1038/cdd.2012.161
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-binding protein interacts with Aβ and suppresses Aβ-mediated pathology

Abstract: The level of vitamin D-binding protein (DBP) is increased in the cerebrospinal fluid of patients with Alzheimer's disease (AD), suggesting a relationship with its pathogenesis. In this study, we investigated whether and how DBP is related to AD using several different approaches. A pull-down assay and a surface plasmon resonance binding assay indicated direct interactions between purified DBP and amyloid beta (Ab), which was confirmed in the brain of AD patients and transgenic AD model mice by immunoprecipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 56 publications
0
54
1
1
Order By: Relevance
“…44 Both of these latter findings highlight that hypovitaminosis D accompanies the onset of the first AD symptoms and therefore may contribute to the initiation of dementia. Other studies have confirmed the existence of a relation between vitamin D and AD; in particular, AD patients have increased levels of vitamin D-binding protein, 45 as well as lower levels of 25OHD in the CSF. 46 A central question relates to whether one can infer causality: that is, does hypovitaminosis D precipitate cognitive disorders or vice versa?…”
Section: Vitamin D and Cognitionmentioning
confidence: 81%
“…44 Both of these latter findings highlight that hypovitaminosis D accompanies the onset of the first AD symptoms and therefore may contribute to the initiation of dementia. Other studies have confirmed the existence of a relation between vitamin D and AD; in particular, AD patients have increased levels of vitamin D-binding protein, 45 as well as lower levels of 25OHD in the CSF. 46 A central question relates to whether one can infer causality: that is, does hypovitaminosis D precipitate cognitive disorders or vice versa?…”
Section: Vitamin D and Cognitionmentioning
confidence: 81%
“…Of these genes, 13 had at least a 2.5-fold difference (an arbitrary cut off) in expression between EFV-treated and untreated 5XFAD mice and the positive false discovery rate q ≤ 0.05. All 13 genes were downregulated (3.2–4.7-fold) in EFV-treated mice, and 9 of them were of relevance to Alzheimer’s disease: Alb (albumin) (Stanyon and Viles, 2012), Pomc (Pro-opiomelanocortin) (Leone et al, 2013), Serpinas 3k and 1e (Serpin Peptidase Inhibitor 3 and 1, respectively) (Guan et al, 2012; Maes et al, 2006), GC (Group-Specific Component or Vitamin D Binding Protein) (Moon et al, 2013), Apoa1 and Apoa2 (Apolipoproteins A-I and A-II) (Lewis et al, 2010; Song et al, 2012), Apob (Apolipoprotein B) (Loffler et al, 2013; Namba and Ikeda, 1991), and Cyp2e1 (Cytochrome P450 2E1) (Van Ess et al, 2002). The 9 genes of relevance to Alzheimer’s disease were then assessed by qRT-PCR, which confirmed their decreased expression, from 5- to 15-fold in EFV-treated mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Altered neurogenesis has been identified in the majority of mouse models of AD, such as Tg2576, A␤PP swe /PS1 dE9 , or triple transgenic AD mice [6]. We have studied a new transgenic mouse model of AD, 5XFAD mice, which develop very early A␤ deposition [7][8][9][10]. These mice co-express a total of five FAD mutations [A␤PP K670N/M671L (Swedish) + I716V (Florida) + V717I (London) and PS1 M146L+ L286V] [11].…”
Section: Introductionmentioning
confidence: 99%